2010
DOI: 10.1097/naq.0b013e3181d9183f
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Delegation and Medication Administration in Assisted Living

Abstract: Assisted living (AL) residences are residential long-term care settings that provide housing, 24-hour oversight, personal care services, health-related services, or a combination of these on an as-needed basis. Most residents require some assistance with activities of daily living and instrumental activities of daily living, such as medication management. A resident plan of care (ie, service agreement) is developed to address the health and psychosocial needs of the resident. The amount and type of care provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Others have noted the importance of nurse oversight in medication administration, which warrants better understanding in the context of AL. 7,23,24,26,30 Also, it is possible that the presence of an observer may have had an influence on the AL staff member's behavior as she prepared or administered the medications, resulting in fewer or more errors. In addition, the observer was not blind to the profession of the staff member, and not all characteristics related to medication errors were examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Others have noted the importance of nurse oversight in medication administration, which warrants better understanding in the context of AL. 7,23,24,26,30 Also, it is possible that the presence of an observer may have had an influence on the AL staff member's behavior as she prepared or administered the medications, resulting in fewer or more errors. In addition, the observer was not blind to the profession of the staff member, and not all characteristics related to medication errors were examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Delegation must never be used to cover a lack of personnel or routinely, but can be seen as being in the interests of older people, as they do not need to meet several different caregivers during the day. Mitty et al. (2010) found that satisfaction with the use of delegation ensured that daily work functioned well.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of trained staff is limited, which may give the consequence that the RN not feel there that there is enough time to implement the necessary training to delegate appropriately (Mitty et al . , Craftman et al . ).…”
Section: Introductionmentioning
confidence: 99%